Medico-social problems of patients with chronic dermatoses - M. M. Tlish; T. G. Kuznetsova (Лечащий Врач, 2021)
The urgency of the problem of chronic dermatoses remains one of the most important in modern clinical dermatology and is due to the high prevalence, increase in severe resistant to treatment forms of diseases, frequent development of complications, malignancy, the formation of severe disabling forms, which has a negative impact on the quality of life of patients. Identification and analysis of causal factors, both socio-psychological and medical, allows to determine the nature of priority measures for the management of patients with chronic dermatoses and will be the key to a successful outcome of the therapy. In this article, we analyze medical and social problems of dermatological patients we observe.